THE ROLE OF UNIVERSITY ORGANIZATIONAL CULTURE IN ANTI-FRAUD SYSTEMS (CASE STUDY AT UNIVERSITY X) - Jeremy Bastanta Ginting; Hana Panggabean (Association of Certified Fraud Examiners Indonesia Chapter, 2019)
University is expected to be a role model in the application of Good Corporate Governance (GCG), because it is the place where the values related to idealism are developed. In practicing GCG’s principles, organizational culture acts as a top layer for an early detection system against fraud. The purpose of this study is to measure the level of the internalization of organizational culture in University X. The data were collected through questionnaires distributed to selected education staff of University X. Sampling was done using sampling stratified technique with 180 participants. The research data were analyzed using descriptive statistical technique by exerting theoretical mean from the result of data collected to measure the level of understanding and application of behavior of university values. The results show that there is a gap between the expected (ideal) and current (actual) level of organizational culture internalization.